The Role of Higher Online Education in the Rural Arctic: Students’ Opportunities and Experiences of Distance Education in Finnish Lapland and Iceland - Tulimaa, Maija, 1991- (2021)
Today the Arctic communities face multiple challenges – outmigration being one of them. Due to urbanisation and outmigration, the future of smaller settlements and their residents is threatened. Many people leave small communities for bigger cities and never return. However, to keep these regions alive and inhabited it is relevant to think about how to make them attractive. The main aim of the thesis is to examine the role of higher online education in community development and viability in the rural Arctic. Furthermore, because sustainable development and human development are essential concepts globally and locally, it is relevant to examine what impact education has on the well-being of human beings, communities, and the environment. In order to scrutinise the role of online education, the study draws on nine interviews that were conducted among distance students living in the remote regions of Finnish Lapland or Iceland. Through the in-depth interviews with students from the University of Lapland and the University of Akureyri, I have identified common concepts and themes. The study reveals that higher online education can have a positive impact on the development and well-being of communities and their residents in the rural Arctic. Firstly, the interviewees felt that higher education is a great opportunity to increase one’s possibilities to find permanent work in different sectors in the rural Arctic. Secondly, studying for a higher education degree can be vital for both personal and professional development. Additionally, academically educated people can bring more versatility to the rural Arctic, which can be an advantage for both communities and individuals themselves. Thirdly, one of the biggest reasons to live in the rural region was family and other relationships. Thus, interviewees felt that online education can give an opportunity for young people and families to stay and live close to their support systems. Finally, the study shows that closeness of nature and recreational activities are important ...